2009
DOI: 10.1007/s10157-009-0192-4
|View full text |Cite|
|
Sign up to set email alerts
|

Utility and feasibility of a new programmable home blood pressure monitoring device for the assessment of nighttime blood pressure

Abstract: Our results suggest that HEM-5041 is useful for evaluating nighttime blood pressures as well as nighttime blood pressure falls, without causing clinically significant discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 39 publications
(36 reference statements)
1
12
1
2
Order By: Relevance
“…These data are in accord with a previous study where nighttime BP was monitoring using an ABP and also a HBP monitor, and found similar quality of sleep with the two methods, yet patients reported that they were more comfortable with HBP monitoring. 9 In conclusion, these data suggest that a novel HBP monitor developed for daytime and nighttime monitoring provides similar daytime and nighttime BP values as the conventional 24-h ABP monitoring and is well accepted by hypertensive patients. Moreover, the detection of non-dippers by this method is in good agreement with 24-h ABP monitoring.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These data are in accord with a previous study where nighttime BP was monitoring using an ABP and also a HBP monitor, and found similar quality of sleep with the two methods, yet patients reported that they were more comfortable with HBP monitoring. 9 In conclusion, these data suggest that a novel HBP monitor developed for daytime and nighttime monitoring provides similar daytime and nighttime BP values as the conventional 24-h ABP monitoring and is well accepted by hypertensive patients. Moreover, the detection of non-dippers by this method is in good agreement with 24-h ABP monitoring.…”
Section: Discussionmentioning
confidence: 83%
“…1,5,6 However, preliminary evidence suggests that novel HBP monitors that have been developed to obtain automated BP measurements during nighttime sleep are feasible and acceptable by users. [7][8][9] This study compared 24-h ABP with HBP monitoring performed by a device designed for daytime and also automated nighttime BP monitoring in the evaluation of nocturnal hypertension and the detection of non-dippers among subjects with hypertension.…”
mentioning
confidence: 99%
“…In addition, in a previous study in which nighttime home SBP was measured at 1-hour intervals ≤6 times per night, the difference between nighttime home SBP assessed by Omron 5041 monitor and nighttime ambulatory SBP assessed by A&D TM-2025 monitor was not statistically significant (1.9 mm Hg;P=0.220). 19 In the current study, there might be a greater number of nighttime home SBP readings that were taken on awakening and in bed. In home BP monitoring, the patients had to be in bed between 2:00 and 4:00 AM to get nighttime BP readings; however, in ambulatory BP monitoring, nighttime BP was defined afterward following their diaries.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few newly developed, programmed home BP measurement devices (HEM-5041 and HEM-7471C-N, OMRON, Kyoto, Japan) that can measure nocturnal BP automatically, 5,6 but their predictive power for CVD remains undetermined.…”
Section: How To Evaluate Nocturnal Bpmentioning
confidence: 99%